(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
The present research aimed to analyze the effectiveness of Historical Empathy as a didactic resource in the teaching of Gender History for students in the Biobío region, Chile. The study was based on a qualitative approach with a phenomenological design and included a sample of 120 secondary school students. To meet the study’s objective, the work logs created by the students in four activities were analyzed. The results indicated an understanding and active engagement in addressing gender roles by the students. However, a historical reductionism was observed in the comprehension of certain aspects of the female experience. Regarding Historical Empathy, the students were able to contextualize themselves in history, avoiding presentism, and could identify the emotions that historical figures would have felt.